Pyruvate kinase activation and lipoperoxidation after selective hepatic ischemia in Wistar rats - Boin,Ilka de Fátima Santana Ferreira (2006)
PURPOSE: Hepatic ischemia and reperfusion can cause several problems in hepatic surgery. The aim of this study was to determine pyruvate kinase activation and lipid peroxidation after hepatic ischemia. METHODS: Twenty-four Wistar rats were submitted to 90 minutes of selective liver ischemia and 15 minutes of reperfusion. Twelve animals were submitted to selective liver ischemia and reperfusion (Group A) and the other 12 were submitted to sham operation (Group B). After 15 minutes of reperfusion, the following parameters were measured: mean arterial pressure (MAP), alanine aminotransferase (ALT), glycemia (GLY), hepatic glycogen (GH), pyruvate kinase (PK) activation, hepatic glutathione (GSH) and malondialdehyde (MDA). Analysis of the results were made by the Student t-test and has been considered significant difference for p<0.05. RESULTS: A and B were differents for all parameters analized. CONCLUSION: The animals of group A showed reperfusion syndrome with a fall in MAP, activation of glycid metabolism through the glycolitic pathway and presence of lipid peroxidation compared to group B.